OPTIMIZING PUBLIC PARTICIPATION THROUGH THE REGIONAL PEOPLE'S REPRESENTATIVE COUNCIL (DPRD) IN THE LEGAL FORMATION PROCESS - Mangaraja Manurung; Amri Amri; Wan Azimah; Sri Rahayu Agustini; Susanti Sansi Vera; Erwin Zunaidi (Yayasan Pendidikan Islam Almatani, 2025)
This study explores the crucial role of community participation through Regional People’s Representative Councils (DPRD) in the process of regional lawmaking. The main objective is to analyze how communities actively engage in the formation of regional regulations, identify existing obstacles, and propose strategies to strengthen participatory mechanisms. This research employs a qualitative approach with a case study design. The research subjects include community members and DPRD legislators or members of regional regulation-making committees within one selected district/city, while the research object focuses on the lawmaking process involving public participation. Data were collected through in-depth interviews, observations of community forums, and documentation of DPRD procedures and related legal instruments. Data analysis was conducted using a thematic qualitative method through stages of data reduction, data presentation, and verification (triangulation). The findings reveal that although formal mechanisms such as public consultations and hearings are established, community participation often remains symbolic. Public aspirations are recorded but rarely translated into substantive influence on DPRD decisions. The study identifies key determinants of effective participation, including transparency of information, community capacity, and the commitment of DPRD members. This research contributes to the understanding of participatory democracy in local governance and offers practical recommendations to enhance inclusivity in lawmaking: improving public access to information, empowering communities in articulating aspirations, and promoting genuinely deliberative forums. The originality of this study lies in its focus on the micro-level dynamics between communities and DPRD in Indonesia’s regional legislative processes, offering insights into the real challenges of participatory governance